Rancangan Alat Potong Tahu Tradisional untuk Indutri Rumahan di Kabupaten Nagan Raya - Herdi Susanto; Jepri Yanto; Wahyudin Wahyudin (universitas teuku umar, 2020)
Tofu processing by small businesses and small-medium industries in the Nagan Raya district of Aceh province still uses traditional methods, resulting in minimal daily production results, one of the obstacles in the field was found that the lack of tofu production results caused by working tools for cutting tofu still using knives one-eyed (kitchen knife), from the above, in this study, a number of model tools to cut tofu were adapted to suit the needs of the home industry, the stages of research in the study of literature, observation of tofu processing in the home industry, design of three models of tool design and analysis perunit costs and time efficiency assumptions about the performance of the tofu cutting device. Design using software produces three models of tofu cutting tools namely, models I and II with main frame stainless P = 100 cm, L = 100 and T = 5 cm, and model III stainless main frame P = 100 cm, L = 8 cm and T = 5 cm ,. Assumption of tool performance from the three design models with consideration of production costs and cutting speed, then from the results of literature studies and observations of the tofu making process traditionally selected model III which is more in line with the conditions of home industry workers in Nagan Raya district, with the specifications of the Long stainless main frame 100 cm Width 1 cm and Height 5 cm, tofu production capacity with two pieces of 256 pieces and a cutting speed of 150 seconds. Keywords— tofu cutting tools, home industry, analysis perunit costs, cutting speed